Sistem Pengelolaan Administrasi Pendidikan Islam - Ismi Izzatul Shoumi; Maemunah Sa’diyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This article discusses the Islamic education administration management system, because administration has a very important role in achieving the goals of educational institutions. The success of education is not only determined by the vision and mission that has been formulated by the educational institution, but this success is determined by the ability and appropriateness of the administration in its management of education. The method used in this research is descriptive qualitative through a literature review approach (library research). Data sources in this research are reports, news, articles and other documents relevant to the topic of discussion. The data collection technique involves searching for various data sources such as books, journals, and research that has been carried out. In this research, researchers collected data using books, journals, and research on Islamic education administration management. The data analysis technique in this research uses the content analysis method (Content Analysis) through inductive and deductive approaches. The technique in this research aims to analyze the meanings contained in all ideas related to management systems in Islamic education administration.